2010
DOI: 10.1245/s10434-010-0920-8
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Sentinel-Node-Based Adoptive Immunotherapy in Advanced Colorectal Cancer

Abstract: BackgroundDespite optimal surgical treatment and modern adjuvant therapies, 50% of patients diagnosed with colorectal cancer die within 5 years. Immunotherapy offers an appealing complement to traditional chemotherapy, with possible long-term protection against tumor recurrences through immunological memory. We have conducted a pilot study of a novel adoptive immunotherapy, using autologous, in vitro expanded lymphocytes isolated from the tumor-draining sentinel lymph node.Study DesignSentinel nodes were recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…IFN-g-producing T H 1 cells are one of the potent antitumor components (5,9,12,14). Therefore, we analyzed the development of OVA-specific IFN-g-producing donor cells following in vivo priming in tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-g-producing T H 1 cells are one of the potent antitumor components (5,9,12,14). Therefore, we analyzed the development of OVA-specific IFN-g-producing donor cells following in vivo priming in tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%
“…These findings have led us to develop tumor-derived antigen-specific vaccine strategies including further exploration of tumor-associated antigens (2) and dendritic cell vaccines for patients with cancer (3, 4). Currently, a potential role of CD4 þ T cells for cancer immunotherapy is being increasingly appreciated (5)(6)(7)(8)(9). Accumulating evidences have shown that tumor-specific CD4 þ T cells eradicate tumors via orchestrating host-derived immune components, especially CD8 þ T cells (7,(10)(11)(12) and natural killer cells (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, it remains to be demonstrated whether they play this role in humans with solid tumors. We have previously described that a tumor-specific Th1 response is present in sentinel LNs in colon and bladder cancer (42,43), and that sentinel node-acquired CD4 + T cells are promising for use in adoptive immunotherapies (1). In this study, we emulated sentinel node-resident total APCs for ex vivo T cell activation and expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in the field of tumor immunology has made immunotherapy an attractive approach in trying to treat cancer. However, these efforts have mainly focused on tumor-reactive T cells (1)(2)(3)(4). Less attention has been paid to B cells and their role in host defense against tumors (5).…”
mentioning
confidence: 99%